Effects of temperature and pressure on the magnetic properties of La1–xPrxCoO3 - Panfilov, Anatoliy S. (2020)
For La1–xPrxCoO3cobaltites (x¼0, 0.1, 0.2, and 0.3), the dependence ofmagnetic susceptibilityχðTÞis studied in the temperature range 5–400 K. Also,the crystal structure of these cobaltites is investigated, and the effect ofpressure up to 2 kbar on their susceptibility is measured atT¼78, 150, and300 K. The specificdependenciesχðTÞandthelargenegativepressureeffectare assumed to arise from Co3þions contribution to the total susceptibilityevaluated using La1 xPrxAlO3as a reference system. The obtained experi-mental data on temperature and pressure effects in magnetism are analyzedwithin a two-level model with energy gapΔbetween the ground state of thesystem with zero spin of Co3þions and the excited higher-spin state. In thismodel, magnetism of Co3þions is determined by the temperature-inducedpopulation of the excited state, and magnitude of the pressure effect is gov-erned by the volume dependence ofΔ. The results of the analysis, supple-mented by the theoretical calculations of the electronic structures of LaCoO3and PrCoO3, indicate significant increase inΔwith decrease in the unit cellvolume both under hydrostatic pressure and by substituting La with Pr having asmaller ionic radius.